ANALISIS PENGENDALIAN KUALITAS (QUALITY CONTOL) PRODUK ROTI MENGGUNAKAN ALAT BANTU STATISTIK - Muzakir Muzakir (Jurnal Optimalisasi, 2015)
Quality problems have led to the tactics and strategy of the company as a whole in order to have a competitive and survive against global competition with other companies' products. One of the activities in creating quality to fit the standard is to implement proper quality control system, have clear objectives and stages, as well as providing innovations in the prevention and solution of the problems facing the company. This study was carried out in the UKM manufacturing of dry bread which aims to create kulaitas penegndalian system that can minimize the amount of disability products produced. The tools that used in this research are seven tools. The results showed that there are two dominant variables that cause the bread kecacaatn deformed and charred by 20.5%. Through the analysis of a causal diagram can be seen the factors causing damage in production is derived from a human factors / workers, machinery production, working methods, materials / raw materials. This study gives an overview on the real condition of the object studied, requiring further studies on preventive measures that can be done in controlling the process of product quality testing.Keywords : Quality, statistic, seven tools, UKM